Analysis of Academic Database Design for SD Negeri 195 Lubuk Mumpo, North Bengkulu Regency - Chries Monicha; Yetman Erwandi (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2022)
The use of database is intended as a means of data storage. It can thus minimize mistakes made andmake time efficiency to find data or information desired. In addition, the database can display the data quickly and accurately. Therefore, to support effective academic information systems need to be designed a database system that is more comprehensive academic so that it is easier to process data needed. The objectives to be achieved in this study is to design an academic database and test normalization in State Elementary School (SDN) 195 LubukMumpo of North Bengkulu in order to reduce data redundancy, duplication, inconsistencies, and the disintegration ofdata that cause thedata storage improvident and makethe inaccurate data of academicreport.The results achieved in this study is producing an academic database on SDN195 LubukMumpo that has been done thenormalization to the third form which can minimize the disintegration, the inconsistency, the duplication of data.